An empirical study on the impact of human capital on cost efficiency: taking the main corn production areas in China as an example. (31st December 2022) - Qian, Wang; Jie, Lv
ABSTRACT : Improving cost efficiency is one of the main ways to reduce the production cost of agricultural products and increase farmers' income. Human capital is an important way to improve cost efficiency. This article takes five major corn production areas as an example, uses data envelopment analysis to measure the cost efficiency and makes an empirical analysis of the impact of human capital on cost efficiency and its action path by using bidirectional fixed-effect model. It is found that the impact of educational human capital on cost efficiency presents a positive 'U' shape, and there are differences among different regions through technical efficiency and allocation efficiency paths. Healthy human capital has a significant positive impact on cost efficiency, but with the increase of the number, its role will gradually weaken, except for the southwest region, and its impact path is allocation efficiency. The impact of technical human capital on cost efficiency shows a positive 'U' type change, and the change of each production area is roughly the same as the whole. Its impact on cost efficiency is mainly realised through allocation efficiency. This article provides a theoretical basis for different policy measures to better play the role of human capital in improving cost efficiency in China.